KEY FACTORS IMPACTING UNIVERSITY STUDENTS' INTENTION TO ENGAGE IN INFAQ THROUGH KITABISA.COM - Wijaya, Deni Ganda; Athoillah, Moh. (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 8 No 1 (2022): The 8th International Conference Of Islamic Economics And Business (ICONIES 2022), 2022)
This research aims to analyze determinant factors affecting university students’ intention in giving infaq using Kitabisa.com. This research was conducted because the expected numbers of zakat, infaq, and sadaqah (ZIS) are huge in Indonesia. Using a Likert-scaled questionnaire, we collected data from 100 students of the Faculty of Economics and Business, Universitas Brawijaya, in the class of 2016-2018 who had used Kitabisa.com. This research uses Partial Least Square model, a quick, efficient, and optimal regression method based on covariance. The model should satisfy both the outer and the inner model testing. This study result shows that altruism and effort expectancy directly influenced the intention of university students in giving infaq using Kitabisa.com, while facilitating conditions did not have any effect on the college students in giving infaq using Kitabisa.com. The finding also concludes that the student’s intention to give infaq does not depend on their income.